G-21 and Bharat Foreign Policy (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
India, officially the Republic of India, has full diplomatic relations with 201 states, including Palestine, the Holy See, and Niue. The Ministry of External Affairs (MEA) is the government agency responsible for the conduct of foreign relations of India. With the world's third largest military expenditure, second largest armed force, fifth largest economy by GDP nominal rates and third largest economy in terms of purchasing power parity, India is a prominent regional power and a rising superpower.[2][3]